Quantification of P-glycoprotein function at the human blood-brain barrier using [18F]MC225 and PET - Mossel, Pascalle; Arif, Wejdan M.; De Souza, Giordana Salvi; Varela, Lara Garcia; van der Weijden, Chris W. J.; Boersma, Hendrikus H.; Willemsen, Antoon T. M.; Boellaard, Ronald; Elsinga, Philip H.; Borra, Ronald J. H.; Dierckx, Rudi A. J. O.; Lammertsma, Adriaan A.; et al. (European journal of nuclear medicine and molecular imaging, 2023)
Introduction P-glycoprotein (P-gp) is one of the most studied efflux transporters at the blood-brain barrier. It plays an important role in brain homeostasis by protecting the brain from a variety of endogenous and exogeneous substances. Changes in P-gp function are associated both with the onset of neuropsychiatric diseases, including Alzheimer’s disease and Parkinson’s disease, and with drug-resistance, for example in treatment-resistant depression. The most widely used approach to measure P-gp function in vivo is (R)- [ 11 C]verapamil PET. (R)- [ 11 C]verapamil is, however, an avid P-gp substrate, which complicates the use of this tracer to measure an increase in P-gp function as its baseline uptake is already very low. [ 18 F]MC225 was developed to measure both increases and decreases in P-gp function. Aim The aim of this study was (1) to identify the pharmacokinetic model that best describes [ 18 F]MC225 kinetics in the human brain and (2) to determine test-retest variability. Methods Five (2 male, 3 female) of fourteen healthy subjects (8 male, 6 female, age 67 ± 5 years) were scanned twice (injected dose 201 ± 47 MBq) with a minimum interval of 2 weeks between scans. Each scanning session consisted of a 60-min dynamic [ 18 F]MC225 scan with continuous arterial sampling. Whole brain grey matter data were fitted to a single tissue compartment model, and to reversible and irreversible two tissue-compartment models to obtain various outcome parameters (in particular the volume of distribution ( V T ), K i , and the rate constants K 1 and k 2 ). In addition, a reversible two-tissue compartment model with fixed k 3 / k 4 was included. The preferred model was selected based on the weighted Akaike Information Criterion (AIC) score. Test-retest variability (TRTV) was determined to assess reproducibility. Results Sixty minutes post-injection, the parent fraction was 63.8 ± 4.0%. The reversible two tissue compartment model corrected for plasma metabolites with an estimated blood volume ( V B ) showed the highest AIC weight score of 34.3 ± 17.6%. The TRVT of the V T for [ 18 F]MC225 PET scans was 28.3 ± 20.4% for the whole brain grey matter region using this preferred model. Conclusion [ 18 F]MC225 V T , derived using a reversible two-tissue compartment model, is the preferred parameter to describe P-gp function in the human BBB. This outcome parameter has an average test-retest variability of 28%. Trial registration EudraCT 2020-001564-28 . Registered 25 May 2020.